1998
DOI: 10.1590/1413-812319983102862014
|View full text |Cite
|
Sign up to set email alerts
|

Rumos e Desafios: Encerrando um Processo de Avaliação da Pós-Graduação Stricto Sensuem Saúde Coletiva (1994-1997)

Abstract: Resumo: Este artigo intenta realizar uma síntese de um processo avaliativo da Pós-Graduação (PG) em Saúde Coletiva brasileira, que vem sendo coordenado pela ABRASCO desde 1995. Particularmente, destaca questões nucleadoras de problemas identificados como prioritários para a PG da área: a estrutura curricular, analisando a possibilidade de instituição de um núcleo disciplinar ou temático para os cursos; a articulação entre os níveis formadores da PG, discutindo aspectos de ordem conceituai e organizacional; a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…(2) the study showed a productive academic community, in the middle of a maturing process, around the concept of "Collective Health", a concept born from the health movement and resting on three pillars: generation of knowledge, practical action in favor and with the participation of society and acting in the political field of the sector; (3) to continue the collective reflection and face the challenges mentioned, the Forum of Postgraduate Coordinators was created and continues to this day; (4) the launching of a scientific journal was already decided at that time and had been considered for some time. All this story and the results of the evaluation are recorded in the first issues of C&SC [6][7][8][9][10][11][12] .…”
Section: The Origin Mythmentioning
confidence: 99%
“…(2) the study showed a productive academic community, in the middle of a maturing process, around the concept of "Collective Health", a concept born from the health movement and resting on three pillars: generation of knowledge, practical action in favor and with the participation of society and acting in the political field of the sector; (3) to continue the collective reflection and face the challenges mentioned, the Forum of Postgraduate Coordinators was created and continues to this day; (4) the launching of a scientific journal was already decided at that time and had been considered for some time. All this story and the results of the evaluation are recorded in the first issues of C&SC [6][7][8][9][10][11][12] .…”
Section: The Origin Mythmentioning
confidence: 99%
“…Contudo, quando as pesquisas tratam de investigar o objeto da Saúde Coletiva na educação superior de pós-graduação senso estrito, há predomínio dos estudos da área Saúde Coletiva que é institucionalizada em 1993 pela CAPES (Nunes, Costa, 1997;Minayo, Costa, 1998;Canesqui, 1998;Viacava, 2010;Minayo, 2010;Barata, Santos, 2010;Nunes, Ferreto, Barros, 2010;Nunes, 2011;Côrrea, 2012;Côrrea, Ribeiro, 2013).…”
Section: Brasileiraunclassified
“…Alertam que havia pressão, principalmente do MEC, para que fossem criados novos programas de pós-graduação senso estrito, "a fim de que sejam reconhecidos por mérito e recebam financiamento público" (Minayo, Costa, 1998, p. 89). Afirmam que tal pressão tem gerado impacto, principalmente nas instituições fora do eixo das capitais das regiões Sudeste e Sul e reunido docentes de várias formações e especialidades que tocam superficialmente no objeto da Saúde Coletiva (Minayo, Costa, 1998).…”
Section: As Práticas Em Saúdeunclassified